Histological and Enzymatic Changes of the Liver in Common Carp(Cyprinus carpio L. 1758) After Chronic Exposure to A Mixture of Goldate and Alexander Pesticides - Salih, Noor Yaseen; Al-Azawi, Ahmed J. Mohammed (Iraqi Journal of Science, 2024)
Pesticides are man-made chemical compounds, widely used in agriculture to control different types of pests, product crops and prevent diseases which damage them. This experiment used herbicide Goldate, insecticide Alexander and their mixture with different concentrations exposed to common carp in 40L glass aquaria. The results showed that there was a significant increase in the alanine aminotransferase (ALT) and aspartate aminotransferase (AST) means value of mixture pesticides compared with control. The liver tissues of the fish exposure to pesticides groups G1, A1, M1 and M2 showed different degrees of jaundice, cellular swelling, necrosis hepatocytes and vascular degeneration of pancreatic acini and aggregation of bile pigments. These effects increased with the increase in pesticides concentrations and exposure time. These effects also increased when exposure was to more than one pesticide at the same time. The study aimed to evaluate the effects of two pesticides as mixture, study the chronic toxicity of Goldate, Alexander and their mixture by assessing  ALT, AST and liver histological changes. This study concluded that the Goldate + Alexander mixture had adverse effects more than each one alone.